Pengaruh Literasi Kewirausahaan dan Efikasi Diri Terhadap Minat Berwirausaha Siswa Jurusan IPS di SMA Negeri 4 Enrekang - Muti Almuna; Ilham Thaief; Muh. Ihsan Said; Muhammad Dinar; Muhammad Hasan (Indonesian Journal of Social and Educational Studies, 2020)
The Study aims to know the impact of entrepreneurial literacy and self-efficacy on interest in entrepreneurial of social science majoring students in SMAN 4 Enrekang. The study was categorized as quantitative work with a population of 160 students, and a samples of 62 students. Data collection is done with documentation and questionnaire technique. The analysis technique used is multiple linear regression analysis using SPSS Version 16 software. Research shows that: (1) Entrepreneurial literacy does has a positive and significant impact on interest in entrepreneurial of social science majoring students in SMAN 4 Enrekang. (2) self-efficacy has a positive and significant impact on interest in entrepreneurial of social science majoring students in SMAN 4 Enrekang.